A new diagnostic marker for differentiating multicentric gliomas from multiple intracranial diffuse large B-cell lymphomas on 18F-FDG PET images. Issue 32 (August 2017) - Wang, Kai; Zhao, Xiaobin; Chen, Qian; Fan, Di; Qiao, Zhen; Lin, Song; Jiang, Tao; Dai, Jianping; Ai, Lin
Abstract : Abstract: Intracranial gliomas and lymphomas may share similar radiological manifestations, while the treatment strategies for them are different. The aim of the study was to investigate the diagnostic value of fluorine-18-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission computed tomography (PET) for differentiation of multicentric gliomas and intracranial multiple diffuse large B-cell lymphomas (DLBCLs) as a study of diagnostic accuracy. A total of 32 patients with multiple intracranial tumors visualized on contrast-enhanced magnetic resonance imaging (MRI) were retrospectively evaluated. Histopathological findings confirmed multicentric gliomas and multiple DLBCLs in 17 and 15 patients, respectively. All patients underwent 18 F-FDG PET with or without 11 C-methionine PET. Maximum standardized uptake values (SUVmax ) and tumor-to-normal tissue (T/N) ratios were compared between the 2 tumors. The diagnostic value of 18 F-FDG PET for differentiating multicentric gliomas from multiple DLBCLs was evaluated by receiver operating characteristic (ROC) analysis. The SUVmax of multiple DLBCLs was significantly higher than that of multicentric gliomas ( P  = .009). However, the percentage of maximum difference-value of SUVmax (or T/N ratio) of multiple DLBCLs was significant lower than that of multicentric gliomas ( P  < .001). The ROC curve demonstrated that the percentage of maximum difference-value of SUVmax (or T/N ratio) on 18 F-FDG PET images could effectively differentiate multicentric gliomas from multiple DLBCLs, with a cut-off value of 44.4%, sensitivity of 64.7%, and specificity of 100% ( P  < .001). Percentage of maximum difference-value of SUVmax (or T/N ratio) on 18 F-FDG PET images might be a potential indicator for distinguishing multicentric gliomas from intracranial multiple DLBCLs, which might help determine the treatment strategy.